2010
DOI: 10.1111/j.1651-2227.2010.02069.x
|View full text |Cite
|
Sign up to set email alerts
|

Possible roles of bilirubin and breast milk in protection against retinopathy of prematurity

Abstract: Aim-To explore the association of serum bilirubin level and breast milk feeding with retinopathy of prematurity (ROP) in preterm infants.Methods-We conducted a case-control study to examine the independent and combined effects of serum bilirubin and breast milk feeding on ROP risk in infants <32 weeks gestation or with birth weight <1500 grams. Cases (66 infants with ROP) were matched with controls (66 infants without ROP) based on factors know to affect ROP risk.Results-When analyzed using the paired t test, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 28 publications
0
23
1
Order By: Relevance
“…25 Contrary to all of these reports; Heller et al 20 concluded that human breast milk intake was not associated with a decreased risk of ROP in extremely very low birth weight infants. Kao et al 22 also evaluated the antioxidant effect of human breast milk and bilirubin on ROP, but only high bilurubin levels were found to have a protective effect on ROP, contrary to our study. A common point to all of these studies including ours is that human breast milk is advised to prevent ROP.…”
Section: Volume 61 • Numbercontrasting
confidence: 99%
See 3 more Smart Citations
“…25 Contrary to all of these reports; Heller et al 20 concluded that human breast milk intake was not associated with a decreased risk of ROP in extremely very low birth weight infants. Kao et al 22 also evaluated the antioxidant effect of human breast milk and bilirubin on ROP, but only high bilurubin levels were found to have a protective effect on ROP, contrary to our study. A common point to all of these studies including ours is that human breast milk is advised to prevent ROP.…”
Section: Volume 61 • Numbercontrasting
confidence: 99%
“…[1][2][3][4][5][6][7][13][14][15][16][17][18] The effect of human breast milk on ROP development is a controversial issue in the literature. [19][20][21][22][23][24][25] As far as we know, studies about the pathophysiological relationship between ROP and human breast milk are limited. 24 ROP develops at two phases and the first phase is the hyperoxic phase.…”
Section: Volume 61 • Numbermentioning
confidence: 99%
See 2 more Smart Citations
“…However, elevated circulating bilirubin concentrations have been associated with protection from neonatal hyperoxic exposure (and retinopathy of prematurity) in both rodent [13] and human [14] studies. Despite these findings, evidence to the contrary also exists and supports a popular debate in this area [15,16].…”
Section: Introductionmentioning
confidence: 99%